Optimalisasi Bantuan Luar Negeri untuk Rehabilitasi Bencana Alam melalui Pemberdayaan Microfinance - Rokhedi P. Santoso (Unisia, 2005)
The following article investigates the disaster constitutes not only humanity problem but also that of development. The impact of disaster generally more crucial toward poor people, so disaster denotes one of many factors that implies increasing poverty. International aid for emergency, rehabilitation or reconstruction should need management in order to minimize the impact of disaster, for instance microfinance. Microfinance has proved successful to decrease impact of disaster risks, to prevent, to recovery economic life after happening disaster.